(untitled) (Research, Society and Development, 2019)
The present study aims to understand the importance of gestational planning from the perspective of different generations of women. The article is qualitative, being carried out with mothers of different ages, range of income, social classes and family compositions. As a result the study reveals that the lack of planning of the post partum period hinders the first months of the life of the newborn and the mother. Finally, the study infers that gestational planning is important for the periods before gestation, gestation and post gestation, regarding the quality of life of the woman and the baby, as individuals more directly involved, as well as in what refers to changes in the family environment for others, such as the father, the grandparents, other children.